Early MRI measures independently predict 1-year and 2-year radiographic progression in rheumatoid arthritis: secondary analysis from a large clinical trial. Issue 11 (31st July 2013) - Baker, Joshua F; Østergaard, Mikkel; Emery, Paul; Hsia, Elizabeth C; Lu, Jiandong; Baker, Daniel G; Conaghan, Philip G
Abstract : Objective: To determine if early MRI measures predict X-ray progression at 1 and 2 years in a large RA trial cohort. Design: This study included 256 methotrexate (MTX)-naïve RA patients from a randomised placebo-controlled trial of golimumab (GO-BEFORE). MRIs of wrist and 2nd–5th metacarpophalangeal joints at 0, 12, 24, 52 and 104 weeks were obtained and scored using the RAMRIS system. Multivariable logistic regression examined if baseline and early change (weeks 12/24) in RAMRIS scores independently predicted progression of the van der Heijde-Sharp (vdHS) score and MRI erosion score at 1 and 2 years of follow-up. Results: High baseline score and poor improvement over the first 24 weeks in synovitis (p=0.003 and p=0.003, respectively) and in bone oedema (p=0.02 and p=0.001, respectively) were independent predictors of X-ray progression at 1 year. Associations were significant or tended towards an association at 2 years. An increase in RAMRIS bone erosion >0.5 at weeks 12 and 24 also predicted X-ray progression (p<0.003). Poor 12-week improvement in bone oedema was associated with X-ray and MRI progression at 1 year (p<0.05). Regression models that incorporated baseline and 12-week and 24-week changes in MRI measures of synovitis (AUC=0.71) and bone oedema (AUC=0.70) improved the prediction of X-ray progression at 1 year above clinical disease activity alone (AUC=0.66, p<0.04). Conclusions: Baseline and early changes in MRI measures independently predicted X-ray and MRI progression at later time-points. The predictive validity established here supports potential use in shorter-duration studies to determine efficacy of RA therapies in preventing structural damage.